A comparative study of cranafacial morphology in Malaysian aborigines and Malays - Mokhtar, Norehan; Samsudin, Ab Rani; Khamis, Mohd. Fadhli (Pusat Pengajian Sains Pergigian, Universiti Sains Malaysia, 2009)
In clinical practice, cephalometric analysis is valuable in assessing facial and dentoskeletal relationships. It provides a measure of skeletal morphology and allows correlations of skeletal factors of malocclusion in and among populations. This study aims to provide cephalometric findings of a selected Orang Asli population ofKelantan particularly the Jahai tribe and compare values with other ethnic groups. It is a cross-sectional study involving 68 selected adults of the Jahai tribe. Cephalograms of adults aged 18-45 years were taken using a standard Orthopantomograph (OPT) machine. These cephalograms were individually traced by manual method using tracing paper and 2B pencil. The tracings of the cephalograms were then analyzed according to Steiner's analysis and SPSS Version 11.0. The analyses of each measurement characteristics of the sample were compared with the standard accepted values for other ethnic groups. It was found that the Jahai tribe of Orang Asli population in Kelantan has a more prominent bimaxillary protrusion compared with other ethnic groups. These findings confirmed that there were significant variations in the craniofacial features of Orang Asli population, particularly the Jahai tribe when compared with the other ethnic groups. These measurements served to complement existing incomplete data of craniofacial measurements in our local data bank. Thus, this tiny effort has a potential role in the completeness of craniofacial analyses of the local Orang Asli population. The information collated can further enhance valid comparisons and establish norms among tribes in Malaysia and in the Asia pacific region